Investigation of the working conditions of nurses in public hospitals on the basis of nurse-friendly hospital criteria - Fatma Er; Serap Sökmen (Elsevier, 2018)
Objective: This descriptive study reveals how nurses working in public hospitals rated their practice environments with respect to nurse-friendly hospital criteria. Methods: This study was conducted on 460 nurses volunteering to participate this study among 735 nurses working in inpatient wards of three public hospitals. Data were collected using a personal information form and the Adapted Nursing Work Index-Revised. Numbers, percentages, means and standard deviations, t-test and one-way variance analysis were used to evaluate the data. Results: Among the nurse-friendly hospital criteria, 'control of nursing practice', 'middle management accountability' and 'quality initiatives' had the highest mean scores, and 'competitive wages' had the lowest mean score. The assessments of the nurses presented statistically significant differences with respect to personal and occupational variables. Conclusion: The nurses found most of the nurse-friendly hospital criteria adequate, but they believed that several areas needed improvement. Keywords: Nurses, Nurse-friendly hospital criteria, Positive work environment